Efficient Electromagnetic Simulation Including Thin Structures by Using Multi-GPU HIE-FDTD Method - Yuta Inoue; Hideki Asai (Applied Computational Electromagnetics Society Journal (ACES), 2021)
This paper describes an efficient simulation method to solve the large scale electromagnetic problems with thin unit cells in the finite-difference time-domain (FDTD) simulation. The proposed method is based on the hybrid implicit-explicit and multi-GPU techniques, which can choose a larger time step size than that in the conventional one, and using the multiple graphic processing units (GPUs). In the proposed method, the computational time is significantly reduced.